2015
DOI: 10.1055/s-0035-1544223
|View full text |Cite
|
Sign up to set email alerts
|

A Near Infrared Spectroscopy-Based Test of Calf Muscle Function in Patients with Peripheral Arterial Disease

Abstract: The objective of this study was to evaluate whether a new simple isometric near infrared spectroscopy (NIRS) foot pedal test of lower leg muscles could be used for functional testing of patients suffering from peripheral arterial disease (PAD) in a daily clinical setting as an alternative to the treadmill test now being used. In a comparison of the new test and the existing treadmill test, we applied NIRS recording in both tests. We hypothesized that a pedal test would have an equal or better reproducibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…110 It was found that during an NIRS-assisted test, the report of claudication in the presence of diabetes was delayed, occurring at a lower degree of oxygenation than in patients with PAD only. Another recent study by Pedersen et al 111 detailed an apparatus and procedure for the diagnostics and treatment evaluation of PAD. It is apparent that with regard to PAD, NIRS has quickly progressed from a research fascination to clinically applicable tool.…”
Section: Other Novel Uses Of Nirsmentioning
confidence: 99%
“…110 It was found that during an NIRS-assisted test, the report of claudication in the presence of diabetes was delayed, occurring at a lower degree of oxygenation than in patients with PAD only. Another recent study by Pedersen et al 111 detailed an apparatus and procedure for the diagnostics and treatment evaluation of PAD. It is apparent that with regard to PAD, NIRS has quickly progressed from a research fascination to clinically applicable tool.…”
Section: Other Novel Uses Of Nirsmentioning
confidence: 99%
“…This technique monitors the local balance between oxygen delivery and consumption and provides information on tissue microvascular hemodynamics [ 4 , 9 , 10 , 11 , 12 ]. Being easily usable also for bedside measurements, the technique was tested in PAD for diagnostic purposes as well for foot perfusion assessment under dynamic conditions or in response or during therapeutic treatments [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%